Perceptions of preschoolers and parents on forest pollution - Demirkaya, Hilmi; Köç, Ahmet; Sunay, Serap; Duygu, Hüseyin; Mol, Aslı; Günaydın, Gülsevil; Günaydın, Muhammedi Abdulkerim (Frontiers in Forests and Global Change, 2024)
Introduction An examination of preschool children’s perceptions and attitudes towards the environment and forests has recently been conducted. However, little research has focused on preschool children’s and their parents’ perceptions of clean and dirty forests. Investigating these perceptions is essential to increase children’s interest in and sensitivity to the environment, thereby fostering their development as responsible individuals who protect the natural world. Methods This study aimed to address this knowledge gap by examining the perceptions of clean and dirty forests held by 40 5–6-year-old students and 40 parents, randomly selected from two preschools: one attended by children from high socioeconomic families and the other by children from low socioeconomic families, in a Mediterranean coastal city in southwestern Turkey. A semi-structured questionnaire was used to collect sociodemographic information and perceptions of clean and dirty forests. Additionally, drawing sheets were distributed to the students to illustrate their concepts of clean and dirty forests. Results The results indicated that individuals with higher educational levels had more complex and conscious perceptions of clean forests. Children considered abstract concepts, such as supernatural forces and fossil fuels, while parents focused on awareness and conservation status. Conversely, parents and children with lower levels of education tended to concentrate on more concrete and everyday factors, such as litter and natural disasters. Individuals with higher socioeconomic status generally associated forest cleanliness with conscious behaviors and conservation, whereas those with lower socioeconomic status linked it more with polluting factors. Discussion This investigation provides valuable insights into the management and control of local forests by incorporating the perspectives of children and their parents, promoting responsible and sustainable tourism practices.